(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
Data from the country’s population census are of great importance in teaching sociology. In our republic, scientific information is very necessary for teaching sociology and studying the state of demographic processes. Using the example of the national census, the article examines methods of teaching sociology in New Uzbekistan as an important source of facts about demographic processes. The traditional purpose of the study is to express an opinion on the historical and modern stages of the official census using new scientific methods in historical demography. Undoubtedly, the participation of the people of the republic in this event is considered a necessary condition for democracy. At the end of the article, recommendations are presented for conducting a national census in New Uzbekistan